2022
DOI: 10.15866/irecap.v12i4.22089
|View full text |Cite
|
Sign up to set email alerts
|

Low-Voltage PLC Noise Modelling

Abstract: This paper models the PLC impulsive noise using a linear superposition of univariate Gaussian distributions where the Bayes' theorem is used to find the posterior probabilities. The Gaussian mixture is formulated using discrete latent variables and modelled using two, three and four components in order to evaluate the effect of the number of components (Q). The parameters of the Gaussian mixture are then estimated using the maximum likelihood technique and the expectation-maximization algorithm. Regression ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…It was observed that as the number of components increases, the accuracy of the model also increases. Similar results were also found in [18] where the GM model which employed the ML estimation method to determine the optimal parameters was used to model the PLC impulsive noise. In this case, two, three, and four-component GM models were used, and the components that do not contribute to the GM were automatically pruned out as their mixture weights were reduced to zero.…”
Section: Model Order Selectionsupporting
confidence: 78%
See 4 more Smart Citations
“…It was observed that as the number of components increases, the accuracy of the model also increases. Similar results were also found in [18] where the GM model which employed the ML estimation method to determine the optimal parameters was used to model the PLC impulsive noise. In this case, two, three, and four-component GM models were used, and the components that do not contribute to the GM were automatically pruned out as their mixture weights were reduced to zero.…”
Section: Model Order Selectionsupporting
confidence: 78%
“…Although the measured amplitude distribution for the Electronic Laboratory has a higher amplitude impulsive noise level and outliers, the two-component GM model is selected as the optimum model. In [18], it was also observed that when the PDF of the amplitude noise has outliers, the likelihood of the model changes minimally as the model complexity increases.…”
Section: Discussion Of Resultsmentioning
confidence: 98%
See 3 more Smart Citations